Simulation of indirect DC-AC-DC converter using cascaded H-bridge multilevel inverter - Mailah, Nashiren Farzilah; Omri, Alif Hakimi (Penerbit UTHM, 2024)
This paper aims to design and analyze the indirect DC-AC-DC converter with multiple inputs that generates higher DC voltage output by using several cascaded H-bridge multilevel inverters. An intermediate AC stage is adopted for the purpose to rectify the high voltage AC level from H-bridge inverter using a three-phase controlled rectifier. A switching algorithm has been developed to obtain the best switching time and duration based on the sinusoidal equation. By optimizing the multilevel concept and equal voltage distribution, the overall total harmonic distortion is reduced, and the overall efficiency is high. This study also comprehensively analyzes the converter's performance under different number of cascaded H-bridge inputs. It is shown that at a high number of cascaded H-bridge, the voltage THD value decrease to 7.57% and the efficiency remains high at above 90%.